O uso de algoritmo de calculo facilitando aprendizagem expansiva entre a logica indigena e a lógica de mercado - Vanessa Sena Tomaz (2019)
This article analyzes how a Maxakali Indigenous student uses arithmetic algorithms to add and subtract learning to manage a scholarship fund. Adopting the cultural-historical activity theory, specifically the conceptual lenses of double stimulation as a tool to analyze the student’s agency formation to gain the capacity, in their collective activities, to resist, criticize, and identify possibilities to deal with the tensions, which structure the relations between Maxakali people and the surrounding society, when mediated by money. The empirical material is composed of field notes, video recordings of classes designed specific for the student taking part of an Indigenous Teacher Training Undergraduate Course; and notes made by the student. The analysis shows that the learning process required the resolution of conflicts of motives experienced by student and that these were trigged by a contradiction within an activity system between the ways to use of money, following Maxakali’s way of life and linguistic code vs a market logic, mediated by hegemonic discursive genres of Western rationality. The addition and subtraction algorithms, spreadsheet, ATM, and bank statement were artifacts introduced and used, forming an effective toolkit needed in the activity, which boosted student’s agency gain. As a result, the student showed a new perception on the relations between the Maxakali and the surrounding society, consciously moving through linguistic and economic frontiers.